A COMPARISON OF THE EFFECTIVENESS OF DIGITAL AND TRADITIONAL LEARNING IN DEVELOPING COUNTRIES - Era Purike; Aslan Aslan (Indonesian Journal of Education (INJOE), 2025)
This research examines the comparative effectiveness of digital and traditional learning in developing countries with the aim of understanding the advantages and challenges of each method in this context. Digital learning offers flexibility and broad access to resources, allowing students to learn at their own pace and cultivate technological skills. However, constraints such as limited technological infrastructure and lack of training for teachers often act as barriers. Meanwhile, traditional learning remains the top choice as face-to-face interaction supports stronger emotional connections and allows for direct customisation to student needs, although it is limited in its appeal and static information. Therefore, many developing countries have started to adopt a hybrid approach that combines the advantages of both methods. The results show that improving the overall quality of education requires investment in digital infrastructure, training for educators, and collaborative support from the government, educational institutions and communities.